Prejudice toward Indian Characters in Gore Verbinski's The Lone Ranger Film - Zuhdi, Ahnaf; Natsir, Muhammad; Sartika Dewi, M, Jonathan Irene (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This research deals with prejudice in The Lone Ranger film by Gore Verbinski. Prejudice is an unfounded attitude of dislike or hatred towards a particular person or group of people based on judgmental beliefs without regard to the unique characteristics of a person or group of people based simply on their membership in that group. The researcher analyzed the prejudiced aspects by characterizing the characters experiencing treatment in this film. This research used a qualitative research design. The data were generated from the speech, action, and thoughts of the characters portrayed in the film. The researcher revealed that the stages of prejudice action in this film are committed by white people and experienced by the Indian People. In conclusion, the four stages of prejudice experienced by the characters were anti-locution, discrimination, physical attack, and extermination. Therefore, the researcher concluded that the difference between both races such as their skin tone, or their behavior is what generated prejudice toward Indian characters.